Ingroup-outgroup racial discrimination: the ambiguous nature of favorable-unfavorable treatment in the retail setting - Silva Junior, Adelson Ferreira da (2022)
This research investigated the phenomenon of ingroup discrimination during congruent racial interactions involving minority group members. More specifically, when manifested in the form of inferior service provided by Black salespersons to Black shoppers in physical stores, an aspect the extant marketplace discrimination literature has not made clear yet. This research deepens the understanding of this phenomenon in the retail setting by integrating two theoretical perspectives: the mechanisms of ingroup preference posited by social identity theory (SIT) and the outgroup preference approached by system justification theory (SJT). The author conducted two empirical studies in sequence by adopting a mixed-method methodology approach to increase the findings’ robustness and answer the call for applying a more diversified range of methodologies in racial discrimination investigations. The first, a quasi-experiment in a natural (out of laboratory) setting, compared the service quality level received from salespersons and perceived by two racial groups of shoppers: Blacks and Whites. The second, a qualitative phenomenological investigation also with Black and White shoppers, provided a more comprehensive view of the nuances of the phenomenon of discrimination involving members of the same minority racial group. As a result, the triangulation of these two studies evidenced that racial congruence between members perceived as belonging to the same minority racial group might not be sufficient to preclude manifestations of subtle discrimination. In this sense, two service quality indicators, observed and measured, revealed that Black and White shoppers did not experience discrimination during interactions with salespersons. That is, there were no differences in the time salespersons approached them, and the time of service they provided to these two racial groups of shoppers. However, the third service quality indicator, the level of recommendations received, demonstrated that Blacks receive less frequently higher-level product recommendations compared to Whites. Furthermore, contrary to the predictions of the marketplace discrimination literature, it happened more incidentally when Black salespersons served Black shoppers. In turn, compared to White shoppers, Blacks were more prone to perceive discriminatory behaviors from salespersons, especially when interacting with White salespersons. Finally, what are generally considered positive service quality indicators (that is, being approached quickly or receiving at first highest priced product recommendations) might be re-signified and perceived as discriminatory behaviors by Black shoppers. From a theoretical perspective, this research offers an additional contribution to understanding how and when the mechanism of ingroup and outgroup preference operate in interactions between members perceived as belonging to the same racial minority group. From a managerial standpoint, the 8 results of this research call attention to the need to recalibrate some service quality indicators and reinforce internal policies that combat the embedded and internalized negative racial references by frontline employees when serving Black shoppers.